2004
DOI: 10.1089/0897715041651006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Implantation of a Peripheral Nerve Graft Reduces Motoneuron Survival but Does Not Affect Regeneration following Spinal Root Avulsion in Adult Rats

Abstract: Adult spinal motoneurons can regenerate their axons into a peripheral nerve (PN) graft following root avulsion injury if the graft is implanted immediately after the lesion is induced. The present study was designed to determine how avulsed motoneurons respond to a PN graft if implantation takes place a few days to a few weeks later. Survival, regeneration, and gene expression changes of injured motoneurons after delayed PN graft implantation were studied. The survival rates of spinal motoneurons were 78%, 65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
6
23
1
Order By: Relevance
“…1a-c). We compared the labeled motoneurons with the expression of p75 NTR , which is correlated with regenerating motoneurons as shown in our previous study [15]. Most of the regenerating motoneurons (labeled by fluorescent dye) were p75 NTR positive ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…1a-c). We compared the labeled motoneurons with the expression of p75 NTR , which is correlated with regenerating motoneurons as shown in our previous study [15]. Most of the regenerating motoneurons (labeled by fluorescent dye) were p75 NTR positive ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Hence, the authors suggest that NGFRp75 could be a marker of ongoing axonal regeneration [22]. Our results imply that high expression of NGFRp75 in nerve grafts at the time of muscle transfer is favorable for the regeneration process, but further studies are needed in this field.…”
Section: Expression Of P75ngfrmentioning
confidence: 78%
“…Expression is also increased in, e.g., mechanical trauma, focal ischemia, stroke, epileptic seizures, and Alzheimer's disease [18]. p75NGFR is also markedly increased in axotomized motoneurons [19 -21], or after spinal root avulsion [22], but the function of this receptor in normal adult motoneurons remains unknown [18,23]. It has also been suggested that p75NGFR participates in apoptosis of motoneurons and Schwann cells [11,18,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, it takes several weeks for the spinal motor neurons to regenerate their axons into the defects and reinnervate the target muscle. The distance between the neuron body and injury site will cause death of the motor neurons in the anterior horn of the spinal cord after lumbosacral nerve injury, which might be caused by lack of neurotrophic factors secreted by Schwann cells and target muscle [34,35]. Therefore, the neurotrophic factors secreted by BMSCs and chitosan conduit provide an appropriate micro environment for axotomised neurons to reach the target muscle.…”
Section: Discussionmentioning
confidence: 99%